Looking at the effect of TaRL-integrated CBL on students' scientific literacy skills: What we can learn? - Annisa Ibrahim; Ervan Johan Wicaksana; Fitri Astriawati (Universitas Ahmad Dahlan, 2025)
In the 21st century, scientific literacy is essential for students to face the complexity of global problems that require scientific understanding in decision-making. PISA data shows Indonesia's low scientific literacy. In 2018, it ranked 74th out of 79 countries with a score of 396 (40% of students only reached level 1), and in 2022, it dropped to 69th out of 81 countries with a score of 383 (34% of students at the elementary level). Less than 1% of Indonesian students reached levels 5-6 in both periods. Efforts to optimize scientific literacy were carried out by implementing a case-based learning (CBL) model integrated with the teaching at the right level (TaRL) approach. A quasi-experimental study was conducted at SMAN 1 Kota Jambi with the topic of the immune system using a non-randomized pretest-posttest control group design. The sample was selected using purposive sampling in grade XI, consisting of an experimental class (CBL-TaRL, n=36) and a control class (CBL, n=36). The results showed that the average score of the experimental class increased from 54.17 to 85.28, while the control class increased from 50.69 to 68.61. The one-way ANCOVA test showed a significant difference [F(1,69)=27.560, p<0.001, ηp²=0.28] with a large effect size. Students taught using CBL-TaRL had a higher increase in scientific literacy, especially in the aspects of analyzing scientific phenomena (36%) and designing scientific investigations (34%).